INTERACTIVE MULTIMEDIA-BASED ARABIC LEARNING IN THE INDUSTRIAL AGE OF TECHNOLOGY - Syaifudin, Muhammad (Proceeding of International Conference on Islamic Education (ICIED); Vol 8 No 1 (2023): Proceeding of International Conference on Islamic Education (ICIED), 2023)
Technology is rapidly developing and impacting all aspects of life, including the economy, work, and education. Education plays a crucial role in shaping human character, and therefore, it needs to keep up with the advances in technology. This means transforming all aspects of education, including curriculum, methods, and learning models. Learning Arabic can be challenging, and students may face various problems in developing their language skills. One solution to overcome these challenges is using interactive multimedia, particularly for developing listening skills (Maharah al-Istima), speaking skills (Maharah al-Kalam), reading skills (Maharah al-Qiroah), and writing skills (Maharah al-Kitabah).